Effects of Zoledronate on Mortality and Morbidity after Surgical Treatment of Hip Fractures. - Cengiz, Ö; Polat, G; Karademir, G; Tunç, OD; Erdil, M; Tuncay, İBRAHİM; TUNCAY, İBRAHİM; Şen, C (My University, 2016)
Intertrochanteric femoral fractures are often seen in the 6th and 8th decades and associated with morbidity, decrease in daily functions, and mortality in elderly patients [1, 2]. Although mortality rates range from 15% to 30%, the femoral fractures particularly show an increase within the year after the fracture occurs [2, 3]. As higher mortality and morbidity rates were reported with conservative treatment in intertrochanteric fractures, surgical treatment and early weight bearing are regarded as the standard approach [4]. Because of high rate of bone union in intertrochanteric fractures due to occurring in extra capsular and cancellous bone, rigid internal determination methods are considered as the first choice in surgical treatment [4, 5]. Osteoporosis has been considered as the main reason for 75% of the fractures in the elderly people. Nowadays, 1.3 million osteoporosis-related fractures were informed in the US annually, and 300,000 of these are hip fractures [6]. However, the data suggest that a small number of patients with hip fracture actually receive pharmacologic treatment for osteoporosis [7, 8]. Zoledronic acid is a potent bisphosphonate used in the treatment of osteoporosis. It has been especially used in the treatment of hip and vertebral fractures due to osteoporosis in postmenopausal women and has been shown in clinical studies to accelerate fracture healing and to inhibit the formation of new fractures [6, 7]. The purpose of this study is to assess the effects of zoledronic acid on mortality and morbidity of intertrochanteric hip fractures in the patients aged over 65 who underwent surgical osteosynthesis.